2019
DOI: 10.1111/anae.14779
|View full text |Cite
|
Sign up to set email alerts
|

Difficult airway management algorithms: a directed review

Abstract: The primary aim of this study was to identify, describe and compare the content of existing difficult airway management algorithms. Secondly, we aimed to describe the literature reporting the implementation of these algorithms. A directed search across three databases (MEDLINE, Embase and Scopus) was performed. All articles were screened for relevance to the research aims and according to pre-determined exclusion criteria. We identified 38 published airway management algorithms. Our results show that most face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 101 publications
(233 reference statements)
0
50
0
6
Order By: Relevance
“…In addition, there are generic resources already available to facilitate airway rescue and transition to the “can't intubate, can't oxygenate” (CICO) scenario . Many of these algorithms are similar in content and should be followed where they do not contradict the specific recommendations for patients with COVID‐19.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are generic resources already available to facilitate airway rescue and transition to the “can't intubate, can't oxygenate” (CICO) scenario . Many of these algorithms are similar in content and should be followed where they do not contradict the specific recommendations for patients with COVID‐19.…”
Section: Methodsmentioning
confidence: 99%
“…The reported incidence of requirement for emergency FONA and death due to airway management are 0.002–0.07% (1:50,000–1:1400) and 0.0006–0.04% (1:180,000–1:2800), respectively . The risk and severity of adverse outcomes during difficult airway management is highlighted by the plethora of guidelines and cognitive aids for airway rescue .…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of requirement for emergency FONA and death due to airway management are 0.002-0.07% (1:50,000-1:1400) [1,27,28] and 0.0006-0.04% (1:180,000-1:2800), respectively [1,28]. The risk and severity of adverse outcomes during difficult airway management is highlighted by the plethora of guidelines and cognitive aids for airway rescue [29]. Awake tracheal intubation involves placing a tracheal tube in an awake, spontaneously-breathing patient, most commonly with flexible bronchoscopy (ATI:FB) or videolaryngoscopy (ATI:VL, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of difficult airway management guidelines found more than 35 different guidelines have been published in the past 20 years (Fig. 3) [104]. As noted by Chrimes and colleagues [1], ''[t]he multiplicity of airway algorithms is both a cause and effect of the professional silos clinicians currently occupy: having different algorithms for specific clinical contexts reinforces the erroneous notion that the issues encountered and/ or the strategies to address them are unique to each context, deterring collaboration.''…”
Section: What Is On the Horizon For Airway Management Training?mentioning
confidence: 99%